[PP.28.21] COMPONENTS OF METABOLIC HEALTH IN METABOLICALLY HEALTHY AND METABOLICALLY UNHEALTHY OBESE SUBJECTS. (September 2017) - Boyarinova, M.; Orlov, A.; Rotar, O.; Alieva, A.; Moguchaya, E.; Vasilieva, E.; Yudina, V.; Solntsev, V.; Baranova, E.; Konradi, A.; Shlyakhto, E.
Abstract : Objective: Metabolically healthy obese (MHO) phenotype is associated with lower cardiovascular risk, compared to metabolically unhealthy obese (MUO). The aim of our study was to compare prevalence and portion dynamic in components of metabolic disorders in obese subjects. Design and method: As a part of epidemiology survey a random sampling of 1600 subjects (25–65 years) stratified by age and sex was involved. Anthropometry (weight, height with body-mass index (BMI) calculation), waist circumference (WC)), blood pressure (BP) measurement and fasting blood-tests: glucose, lipids, CRP, insulin were performed. Wildman (USA, 2008) MHO criteria were used in subjects with obesity (BMI> = 30 kg/m 2 ) - less than 2 of the following criteria: HDL<1.30/1.04 mmol/l or therapy; triglycerides > = 1.7 mmol/l; glucose > = 5.55 mmol/l or treatment; BP > = 130/85 mm Hg or therapy; CRP > 90th percentile; HOMA IR > 90th percentile. Results: Data was available in 395 obese subjects. No significant gender differences in MHO prevalence was revealed. In MHO phenotype, only 24 subjects (28, 3%) had ideal metabolic health - 0 components, and 61 subject (71, 7%) had 1 component. In MHO subjects (1 component) hypertension and dyslipidemia showed maximal prevalence. Along with increasing of metabolic components number (from 2 to 5 - table 1.) only parameters of insulin resistance has significant progressive elevation comparing with relatively stable prevalence of hypertension, lipid and glucose components. Table 1. Dynamic of metabolic health components prevalence in patients with obesity. Figure. No caption available. Conclusions: Hypertension and dyslipidemia are most common metabolic disorders independently of number of metabolic health criteria. With increasing of metabolic unhealthy components burden insulin resistance is dynamically impairing.